Cone Penetration Testing in Polar Snow - McCallum, A B; Barwise, A; Santos, R (Offshore Technology Conference, 2011)
Rate-controlled Cone Penetration Testing (CPT) using unique portable equipment was recently conducted in Antarctica. This testing was undertaken in an attempt to investigate the strength and thence bearing capacity of polar snow via insitu means. The application of this technique may prove useful in assessing numerous physical parameters of snow and other geomaterials found within the Polar Regions including stratigraphy, density, strength and bearing capacity. This paper explores some of the data found within this preliminary investigation and highlights the possibilities for future employment of the method, including the possibility of introducing Laser Induced Florescence tools (LIF) as additional sensors for the insitu detection and speciation of hydrocarbon contaminants. Further, the measuring of sleeve friction in addition to tip-resistance may provide insight into material microstructure, significantly enhancing any strength estimate. The use of this easily deployable equipment in polar environs can provide significant site investigation data that may not otherwise be obtainable.